Exploring the athletic identity, anxiety, and mental health of division II collegiate athletes in the COVID-19 era - Hebert, J. A.; Newland, A. (The Sport Psychologist, 2023)
The COVID-19 pandemic has had serious implications on the health and well-being of student-athletes. The present study explored the athletic experiences of NCAA Division II college athletes during the competitive hiatus caused by the pandemic, as well as in their return to sport participation. Twenty male and female student-athletes from a variety of sports (freshman = 2, sophomores = 4, seniors = 9, and graduate = 5) participated in semistructured interviews to explore how the pandemic affected their athletic identity, anxiety, and mental health. Through the use of thematic content analysis, the following major themes were identified: (a) influence of COVID on athletic identity, (b) increased anxiety during COVID, (c) social aspects of sport participation, and (d) factors that influence mental health. Findings indicated a combination of positive and negative effects on the athletic identity, anxiety, and mental health and well-being of student-athletes.